CUSTOMIZED INTRAOCULAR LENS IMPLANTATION: IMPROVED VISION AND QUALITY OF LIFE FOR CATARACT PATIENTS. - Bispo, Kamilla Silva; Oliani, Ana Lara Gimenes; Prado, Karollyne Francisco; Batista, Alessandra Rezende; Silva, Jessica Gabriele Rosa (Brazilian Journal of Implantology and Health Sciences, 2024)
The implantation of personalized intraocular lenses represents a significant advance in the treatment of cataracts, one of the main causes of visual impairment worldwide. Cataracts, characterized by opacification of the lens, impact patients' vision and quality of life. Conventional intraocular lenses have been effective, but custom lenses offer an adaptable approach, considering each patient's individual characteristics. Objective: To analyze studies published in the last 10 years on the implantation of personalized intraocular lenses in patients with cataracts, focusing on improving vision and quality of life. Methodology: This review followed the PRISMA guidelines. The PubMed, Scielo and Web of Science databases were consulted. Descriptors included “cataract,” “intraocular lens,” “custom,” “improved vision,” and “quality of life.” Inclusion criteria: studies that investigated the use of personalized intraocular lenses in patients with cataracts, with results related to vision and quality of life. Exclusion criteria: studies unavailable in full text, in non-accessible languages and that did not directly address the results of interest. Results: The studies reviewed indicated a significant improvement in the visual acuity and quality of life of cataract patients undergoing custom intraocular lens implantation. Highlights include precision in vision correction, reduced dependence on glasses and high patient satisfaction. Conclusions: Implantation of personalized intraocular lenses has proven to be an effective intervention, offering tangible benefits in terms of vision and quality of life for patients with cataracts. This review highlights the importance of this personalized approach in ophthalmology, highlighting its positive impact on patients' ocular health and well-being.